Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/hepr.13741
|View full text |Cite|
|
Sign up to set email alerts
|

Hyperprogressive disease in patients with unresectable hepatocellular carcinoma receiving atezolizumab plus bevacizumab therapy

Abstract: Background: Atezolizumab plus bevacizumab was approved for hepatocellular carcinoma (HCC) patients in 2020, but treatment outcomes of atezolizumab plus bevacizumab in real-world settings remain unclear. Hyperprogressive disease (HPD), an acceleration of tumor growth occurring in some types of malignancies treated with immune checkpoint inhibitors, was assessed in HCC patients receiving atezolizumab plus bevacizumab.Methods: Tumor growth kinetics (TGK) and tumor growth rate (TGR) were calculated at pre-and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 37 publications
4
30
0
Order By: Relevance
“…This difference may have been due to the small number of cases in the current study. In addition, it should be noted that previously reported NLR cut-off values for predicting patient outcomes differ between studies [15, 43-45], and NLRs change due to various patient conditions (e.g., infections and certain medications, particularly steroid-based immunosuppressive regimens). Therefore, more robust NLR cut-off values are desirable for use in daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This difference may have been due to the small number of cases in the current study. In addition, it should be noted that previously reported NLR cut-off values for predicting patient outcomes differ between studies [15, 43-45], and NLRs change due to various patient conditions (e.g., infections and certain medications, particularly steroid-based immunosuppressive regimens). Therefore, more robust NLR cut-off values are desirable for use in daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…As in the previous reports [41,42], readministration of lenvatinib after diagnosed disease progression during immunotherapies has the potential of disease control effect in some patients. Recently, other researchers reported the utility of NLRs for predicting patient outcomes following Atezo/Bev treatment of HCC [15,[43][44][45]. Furthermore, Maesaka et al [15] reported an NLR cut-off value of ≥3 as a useful predictor for HPD.…”
Section: Kawamura Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table 1 , the correlations between HPD and ICIs have been shown across multiple types of tumor. A number of studies have proved the influence of HPD on OS, progression-free survival (PFS), and the rate of tumor progression [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. As ICIs become more prevalent, improved knowledge of HPD is urgently needed to precisely determine which patients should receive immunotherapy.…”
Section: Introductionmentioning
confidence: 99%